The impact of individualism/collectivism of the host country on the internationalization process and post-entry speed - Luz, Mariana (My University, 2025)
International business literature has showcased the importance of internationalization as a way to ensure business development and success. Therefore, this has been a constant topic within theoretical reviews over the years. Furthermore, networks have been proven in literature to be a relevant component of this process, through different tie strengths and densities. Moreover, culture has been continuously identified as a crucial aspect of internationalization. One of the identified dimensions of culture is the country’s individualism or collectivism. Internationalization can be viewed through many lenses; however, a significant one regards its rapidity. Although its rapidness may be measured through the speed at which a firm internationalized since its foundation, it may also concern the quickness of a company’s growth and development after entering a foreign market. Nonetheless, there is a gap in understanding the dynamic relationship between the individualism or collectivism of the host country and the post-entry speed at which internationalization occurs. Thus, the present study aims to address the research question: “How does the individualism/collectivism of the host country impact the business network internationalization process and the post-entry speed?”. The research question is answered through an understanding of whether the individualism/collectivism of the host country influences the internationalization network tie strength and density, as well as comprehending how the network characteristics affect the internationalization’s post-entry rapidity. The methodology applied to reach the conclusions for this question was an interpretivism and deductive approach, with a qualitative data collection method, which mainly leveraged semi-structured interviews, complemented by secondary data. To adequately test the theoretical framework, the study conducted a two-case study qualitative and subjective analysis, attending to the subjective nature of the study’s central concepts, namely, network characteristics and culture. As case studies, the research analyzed the internationalization processes of two businesses, one in an individualist country and the other in a collectivistic society. The main findings of the work concluded that the individualism or collectivism of the host country influences the strength of network ties; however, it does not affect the network density. Furthermore, the study concluded that the network tie strength, which is influenced by the individualism/collectivism of the host country, has a direct impact on the post-entry internationalization speed. In concordance, if the network has strong ties, there is fast international resource commitment and a moderate international commercial intensity. Contrastingly, if the network has weak ties, there is a higher potential for rapid international sales intensity and a slow international resource investment. In conclusion, the study was successful in answering the intended research question through a revised framework that integrated all of the work’s findings.
Keywords: fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business